2021
DOI: 10.3390/microorganisms9071462
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Microbial Communities and Heavy Metals

Abstract: The rhizosphere is a microhabitat where there is an intense chemical dialogue between plants and microorganisms. The two coexist and develop synergistic actions, which can promote plants’ functions and productivity, but also their capacity to respond to stress conditions, including heavy metal (HM) contamination. If HMs are present in soils used for agriculture, there is a risk of metal uptake by edible plants with subsequent bioaccumulation in humans and animals and detrimental consequences for their health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 174 publications
(331 reference statements)
0
59
0
Order By: Relevance
“…In this study, LZ showed a richer diversity of endophytic fungi than CX. On the one hand, the soil environment (including microorganisms and physiographical factors) of L. chuanxiong can be changed, and the endophytic fungi will be reshuffled because of the transplantation ( Caracciolo and Terenzi, 2021 ). On the other hand, the relative abundance of some endophytic fungi showed regular changes with plant transplantation and finally existed stably in specific growth stages of L. chuanxiong ( Zhalnina et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, LZ showed a richer diversity of endophytic fungi than CX. On the one hand, the soil environment (including microorganisms and physiographical factors) of L. chuanxiong can be changed, and the endophytic fungi will be reshuffled because of the transplantation ( Caracciolo and Terenzi, 2021 ). On the other hand, the relative abundance of some endophytic fungi showed regular changes with plant transplantation and finally existed stably in specific growth stages of L. chuanxiong ( Zhalnina et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystems based in the soil microbiome are influenced and controlled by multiple abiotic and environmental factors, such as soil structure and type, soil pH, soil nutrients, geographical factors (altitude, latitude, and longitude), climatic factors (UV radiation, CO 2 , and temperature) ( Islam et al, 2020 ). Abiotic and environmental factors result in the establishment of multiple microenvironments that offer a diversity of ecological niches ( Caracciolo and Terenzi, 2021 ). In the previous experiments, we found that the diversity of species, main ecological functional groups, and differences in production areas of the fungal community showed a gradual change pattern between the non-rhizosphere soil, the rhizosphere soil, and the rhizome of L. chuanxiong , which proved that during the cultivation process, plants obtain part of the species from the soil of the production area and accumulate or subtract continuously to form a specific endophytic flora ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contaminated land is a potential threat to human health, and its continual discovery over recent years has led to international efforts to remedy many of the sites, either as a response to the risk of adverse health or environmental effects caused by contamination or to enable the site to be redeveloped for new use (Maheshwari et al, 2014, Damodaran andSuresh, 2011). In this context, bioremediation process is reported to be an important strategy for the removal of the heavy metal from the environment, where living part can be considered as a solar-driven pump, which can extract toxic elements from the contaminated soil (Caracciolo andTerenzi, 2021, Ojuederie and. Briefly, the present article offers an overview and discusses the heavy metal toxicity, metal-microbes interactions, and mechanisms used by plants and microbes for remediation of heavy metals pollutants.…”
Section: Introductionmentioning
confidence: 99%